Exploring Students’ Perception Toward Teacher’s Code Switching in Teaching-Learning Process: a Case Study of the Eleventh Grader at SMA Swasta Anastasia in Academic Year 2025/2026 - Aldyan Okuli Alberdsius Sidabungke; Meikardo Samuel Prayuda; Junita Siahaan (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Code-switching by teachers in English learning remains a topic of debate, as it is seen as aiding comprehension, but also raises concerns about increasing students' dependence on their native language. This study aims to analyze students' perceptions of teachers' use of code-switching and its impact on their dependence on Indonesian in English learning. The study employed a qualitative approach with a descriptive study design. Thirty students were selected as participants. Data were collected through semi-structured interviews and analyzed using thematic analysis with the aid of NVivo software for coding and theme validation. The results indicate that students positively perceive code-switching as aiding comprehension of complex material, reducing anxiety, and increasing participation and confidence in using English. However, the use of Indonesian does not create permanent dependence. Students utilize their native language as a temporary buffer to grasp concepts before returning to English for communication and practice activities. These findings suggest that purposefully designed code-switching can serve as an effective pedagogical strategy to support comprehension, engagement, and learning independence without diminishing the use of English as the target language.